Al-Maqrīzī's al-Ḫabar ʻan al-bašar. - Maqrīzī, Aḥmad ibn ʻAlī, 1364-1442 (Bibliotheca Maqriziana Ser., 2017)
Al-Maqrizi's (d. 845/1442) last work, al-Habar 'an al-baSar, was completed a year before his death. This volume, edited by Jaakko Hämeen-Anttila, covers the history of pre-Islamic Iran from the Creation to the Parthians. Al-Maqrizi's work shows how Arab historians integrated Iran into world history and how they harmonized various currents of historiography (Middle Persian historiography, Islamic sacred history, Greek and Latin historiography).00Among al-Habar's sources is KitAb HurUSiyUS, the Arabic translation of Paulus Orosius' Historiarum adversum paganos libri VII. This source has only been preserved in one defective copy, and al-Maqrizi's text helps to fill in some of its lacunae.0.